Targeted partial arthroscopic trapeziectomy and distraction (TPATD): Surgical technique - De Villeneuve Bargemon, Jean-Baptiste; Jaloux, Charlotte; Levadoux, Michel (Hand surgery and rehabilitation, 2023)
Basal joint osteoarthritis is a real public health problem, yet there is no consensus on its treatment. Although total trapeziectomy, as well as arthroplasty, provides long-lasting efficacy, it does not seem to be adapted to a young population with complications that are often very difficult to manage. In the era of minimally invasive surgery, there is a real interest in finding conservative therapeutic alternatives for young subjects that allow them to pass a painful milestone? and thus postpone the least conservative interventions. This article details the surgical technique of an arthroscopic and conservative technique: The Targeted Partial Arthroscopic Trapeziectomy and Distraction (TPATD) based on two points: targeted resection of painful arthritic lesions and distraction of the joint to restore ligament tension and hopefully regrow fibrocartilage on resected lesions.